Contemporary issues in intellectual property law in Africa - Owoeye, Olasupo (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2025)
"This book discusses the impact of intellectual property and international investment agreements within Africa. It investigates how African nations can enhance their current intellectual property legislation across various regions of the continent, while simultaneously fostering the development of local industries and stimulating innovation and creativity within the region. Despite intellectual property remaining a major issue in global trade governance, African countries have room to maximise the advantages that global intellectual property law can offer. Highlighting discourse on investment, intellectual property, and competition policies in Africa, the book underscores the need for African nations to develop intellectual property frameworks that can facilitate economic transformation. Using data from international intellectual property conventions, WTO dispute settlements and African regional organisation conventions, the book is a comprehensive call to action for African intellectual property lawyers and policymakers. The book will be of interest to students and scholars in the field of intellectual property law and international investment law"--
Intellectual Property Rights and Investment Law in the AfCFTA / Emmanuel Kolawole Oke -- Public Interest Regulation of Patents and Investment Treaties in Africa / Dominic Npoanlari Dagbanja, Brett Kenneth Davies and Sadhvi Sinha -- Recalibrating African Investment Treaty System to promote Access to Medicine / Oladapo Fabusuyi -- The Marginalisation of African States in the Negotiation of the TRIPS Agreement / Anu Adeyemi -- Intellectual Property and Local Pharmaceutical Production : Defining the Need and Meeting the Challenge / Tolulope Adekola -- After the WTO COVID-19 Waiver : Africa's Way Forward / Kunle Ola -- Public Health Governance, Intellectual Property, and the African Context : From Outrage to Action in Developing Regional Capability for Health Protection / Uchechukwu Ngwaba -- The AFCFTA and Trade in Counterfeit Drugs : Adopting a Blockchain Technology Based Strategy to Ensure Patient Safety / Ezinne Mirian Igbokwe -- Artificial Intelligence and the Patentability of AI Inventions / Olasupo Owoeye and Omolara Ajayi -- Artificial Intelligence Generated Works and the Copyright Dilemma : A Case Study of the United Kingdom and South Africa / Victoria Taiwo -- "Gamechanger" lawsuit (Francisco Leong v (AFP)) as Platform for Interrogating Copyright Ownership of Photographic Works of Employees in Mass-Media Institutions in Nigeria / Oluwaseyi Leigh.
Keywords: African Continental Free Trade Area; Intellectual property -- Africa; Investments, Foreign -- Law and legislation -- Africa; Investments, Foreign (International law); LAW / Intellectual Property / General; LAW / Business & Financial; LAW / General